Impact of the diaphyseal femoral deformity on the lower limb alignment in osteoarthritic varus knees. (11th April 2023) - Batailler, Cécile; Naaim, Alexandre; Daxhelet, Jeremy; Lustig, Sébastien; Ollivier, Matthieu; Parratte, Sebastien
Abstract : Aims: The impact of a diaphyseal femoral deformity on knee alignment varies according to its severity and localization. The aims of this study were to determine a method of assessing the impact of diaphyseal femoral deformities on knee alignment for the varus knee, and to evaluate the reliability and the reproducibility of this method in a large cohort of osteoarthritic patients. Methods: All patients who underwent a knee arthroplasty from 2019 to 2021 were included. Exclusion criteria were genu valgus, flexion contracture (> 5°), previous femoral osteotomy or fracture, total hip arthroplasty, and femoral rotational disorder. A total of 205 patients met the inclusion criteria. The mean age was 62.2 years (SD 8.4). The mean BMI was 33.1 kg/m 2 (SD 5.5). The radiological measurements were performed twice by two independent reviewers, and included hip knee ankle (HKA) angle, mechanical medial distal femoral angle (mMDFA), anatomical medial distal femoral angle (aMDFA), femoral neck shaft angle (NSA), femoral bowing angle (FBow), the distance between the knee centre and the top of the FBow (DK), and the angle representing the FBow impact on the knee (C'KS angle). Results: The FBow impact on the mMDFA can be measured by the C'KS angle. The C'KS angle took the localization (length DK) and the importance (FBow angle) of the FBow into consideration. The mean FBow angle was 4.4° (SD 2.4; 0 to 12.5). The mean C'KS angle was 1.8° (SD 1.1; 0 to 5.8). Overall, 84 knees (41%) had a severe FBow (> 5°). The radiological measurements showed very good to excellent intraobserver and interobserver agreements. The C'KS increased significantly when the length DK decreased and the FBow angle increased (p < 0.001). Conclusion: The impact of the diaphyseal femoral deformity on the mechanical femoral axis is measured by the C'KS angle, a reliable and reproducible measurement. Cite this article: Bone Jt Open  2023;4(4):262–272.